2002
DOI: 10.1002/app.10581
|View full text |Cite
|
Sign up to set email alerts
|

Morphological studies in thermally initiated emulsion (co)polymerization without conventional initiators

Abstract: Poly(methyl methacrylate-co-styrene) composite latices were prepared by thermally initiated seed emulsion (co)polymerization of styrene (ST), methyl methacrylate (MMA), or ST and MMA employing a PST or PMMA seed in the absence of conventional initiators. The changes of particle morphology, observed by transmission electron microscopy (TEM), were investigated by varying seed particle component, the weight ratio of monomer to seed polymer, monomer composition, and employing preswelling of the seed particles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Phase separation of two or three different polymers in one spherical particles from emulsion polymerization has been used for other polymeric hemispheres. Du et al16,17 and Han et al18 prepared micron and submicron‐sized polymer particles with different morphologies by seeded dispersion or emulsion polymerization. The produced latex exhibited a wide variety of particle morphologies such as core‐shell, hemispherical, and inverted core‐shell structures.…”
Section: Introductionmentioning
confidence: 99%
“…Phase separation of two or three different polymers in one spherical particles from emulsion polymerization has been used for other polymeric hemispheres. Du et al16,17 and Han et al18 prepared micron and submicron‐sized polymer particles with different morphologies by seeded dispersion or emulsion polymerization. The produced latex exhibited a wide variety of particle morphologies such as core‐shell, hemispherical, and inverted core‐shell structures.…”
Section: Introductionmentioning
confidence: 99%
“…By controlling the polymerization process variables, seeded dispersion or emulsion polymerization can produce structured latices exhibiting a wide variety of particle morphologies such as core-shell, hemispherical, or inverted core-shell particles in which second-stage polymer is incorporated at the center of the particle and the seed polymer is located on the periphery of the composite particle. The morphology of two-stage latex particles is controlled by two major factors concomitantly acting in the system [1][2][3][4][5]: thermodynamic factors that determine the equilibrium morphology of the final composite latex particles and kinetic factors that determine the ease with which the thermodynamically favored equilibrium morphology can be achieved. Seeded polymerization for the dispersion of highly monomer-swollen polymer particles gives composite polymer particles having a comparatively thermodynamically stable morphology [6].…”
Section: Introductionmentioning
confidence: 99%
“…The mixed morphologies with C ‐like (hemisphere‐like) and inverted core–shell structure, in which the secondary polymer (PSt) is a core and the seed polymer (PGMA‐DVB) is a shell, were clearly observed in Figure 1(a and b), between which no substantial difference was observed. In our previous research, the difference of particle morphology between the runs with and without the preswelling process was not observed, when the weight ratio M/P was lower 19, 29. Because of the polymerization procedure, a slow stream of nitrogen was introduced into the reaction mixture for 1 or 2 h before heating (30 min) to completely remove the effect of oxygen on the thermal initiation system, since most of the equilibrium swelling was already attained during the nitrogen purge and the heating.…”
Section: Resultsmentioning
confidence: 84%
“…It was reported that the weight ratio of secondary monomer to seed particles (M/P) is a key factor to determine morphology of the resulting composite polymer particles in the PMMA/PSt system 19, 29. In view of this observation, the effect of M/P on the morphology of final composite particles was also investigated in this system.…”
Section: Resultsmentioning
confidence: 99%